Catabolic task division between two near‐isogenic subpopulations co‐existing in a herbicide‐degrading bacterial consortium: consequences for the interspecies consortium metabolic model. (15th December 2017) - Albers, Pieter; Lood, Cédric; Özturk, Basak; Horemans, Benjamin; Lavigne, Rob; van Noort, Vera; De Mot, René; Marchal, Kathleen; Sanchez‐Rodriguez, Aminael; Springael, Dirk
Summary: Variovorax sp. WDL1 mediates hydrolysis of the herbicide linuron into 3, 4‐dichloroaniline (DCA) and N, O ‐dimethylhydroxylamine in a tripartite bacterial consortium with Comamonas testosteroni WDL7 and Hyphomicrobium sulfonivorans WDL6. Although strain WDL1 contains the dcaQTA1A2B operon for DCA oxidation, this conversion is mainly performed by WDL7. Phenotypic diversification observed in WDL1 cultures and scrutiny of the WDL1 genome suggest that WDL1 cultures consist of two dedicated subpopulations, i.e., a linuron‐hydrolysing subpopulation (Lin + DCA‐) and a DCA‐oxidizing subpopulation (Lin‐DCA+). Whole genome analysis of strains representing the respective subpopulations revealed that they are identical, aside from the presence of hylA (in Lin + DCA‐ cells) and the dcaQTA1A2B gene cluster (in Lin‐DCA+ cells), and that these catabolic gene modules replace each other at exactly the same locus on a 1380 kb extra‐chromosomal element that shows plasmid gene functions including genes for transferability by conjugation. Both subpopulations proliferate in consortium biofilms fed with linuron, but Lin + DCA‐ cells compose the main WDL1 subpopulation. Our observations instigated revisiting the interactions within the consortium and suggest that the physical separation of two essential linuron catabolic gene clusters in WDL1 by mutually exclusive integration in the same mobile genetic element is key to the existence of WDL1 in a consortium mode.